SOCIAL PROBLEMS OF RAISING YOUNG PEOPLE IN UZBEKISTAN IN THE SPIRIT OF MILITARY PATRIOTISM - Maripzhonov Javlonbek Makhammadzhan ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
social problems of raising young people in Uzbekistan in the spirit of military patriotism in our article. The changing view of the concept of Homeland in globalistic processes. Meditating on views between patriotism and military patriotism.